A historical review of investigations on laterality of emotions in the human brain. Issue 1 (2nd January 2019) - Gainotti, Guido
ABSTRACT: Different models of emotional lateralization, advanced since the first clinical observations raised this issue, will be reviewed following their historical progression. The clinical investigations that have suggested a general dominance of the right hemisphere for all kinds of emotions and the experimental studies that have proposed a different hemispheric specialization for positive vs. negative emotions (valence hypothesis) or for approach vs. withdrawal tendencies (motivational hypothesis) will be reviewed first and extensively. This historical review will be followed by a short discussion of recent anatomo-clinical and activation studies that have investigated (a) emotional and behavioral disorders of patients with asymmetrical forms of fronto-temporal degeneration and (b) laterality effects in specific brain structures (amygdala, ventro-medial prefrontal cortex, and anterior insula) playing a critical role in different components of emotions. Overall, these studies support the hypothesis of a right hemisphere dominance for all components of the emotional system.